Analysis Of Medium Rise Reinforced Concrete Building Subjected To Lateral Loads - Mohamad Nashuki, Nadia (Universiti Sains Malaysia, 2006)
Since the earthquake and tsunami that happened on 26th December 2004 in Sumatra, it has increased the awareness and urged engineers in Malaysia to identify the importance of considering the earthquake impact to the building structures. In this project, a plan of a medium rise building is selected. This analysis is about the earthquake impact or seismic impact, including other forces such as wind load, gravitational load or selfweight, finishes load, life load and brick wall load with the consideration of the drift. The analysis is being done with the aid of STAAD III Release 22.3 software. From the analysis, it shows that seismic load gave that major lateral deflection to the building structure, compared to other forces such as wind loads, selfweight and live load. The total lateral deflection due to seismic load is 39.9mm while wind load is 21.5mm. As for the inter-storey drift, the value of 3mm is due to wind and 5mm for seismic load. Even though the drift is in the safe range for the structure, the drift difference for seismic load is nearly twice the wind loads. This gives an early notice in the importance of seismic loads consideration for designing any structure in Malaysia.